2019
DOI: 10.15252/embr.201847560
|View full text |Cite
|
Sign up to set email alerts
|

Shieldin – the protector of DNA ends

Abstract: DNA double‐strand breaks are a threat to genome integrity and cell viability. The nucleolytic processing of broken DNA ends plays a central role in dictating the repair processes that will mend these lesions. Usually, DNA end resection promotes repair by homologous recombination, whereas minimally processed ends are repaired by non‐homologous end joining. Important in this process is the chromatin‐binding protein 53BP1, which inhibits DNA end resection. How 53BP1 shields DNA ends from nucleases has been an end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
152
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 94 publications
2
152
0
1
Order By: Relevance
“…One clear example resided in a subcluster enriched in NHEJ factor-coding genes ( Figure 3C). This subcluster contained many core NHEJ factors (XRCC4, LIG4, NHEJ1), 53BP1-pathway modulators such as 53BP1, RIF1 and the shieldin components SHLD1-3 as well as the NHEJ regulator MRI/CYREN (Arnoult et al, 2017;Hung et al, 2018;Setiaputra and Durocher, 2019).…”
Section: The Bone Marrow Failure Syndrome Gene Ercc6l2 Encodes An Nhementioning
confidence: 99%
“…One clear example resided in a subcluster enriched in NHEJ factor-coding genes ( Figure 3C). This subcluster contained many core NHEJ factors (XRCC4, LIG4, NHEJ1), 53BP1-pathway modulators such as 53BP1, RIF1 and the shieldin components SHLD1-3 as well as the NHEJ regulator MRI/CYREN (Arnoult et al, 2017;Hung et al, 2018;Setiaputra and Durocher, 2019).…”
Section: The Bone Marrow Failure Syndrome Gene Ercc6l2 Encodes An Nhementioning
confidence: 99%
“…The DDR is initiated at DNA break sites by the ATM kinase, which phosphorylates histone variant H2AX to generate cH2AX (Shiloh & Ziv, 2013;Blackford & Jackson, 2017). Restrained resection is achieved by 53BP1dependent recruitment of RIF1, REV7, and the Shieldin complex (Dev et al, 2018;Findlay et al, 2018;Ghezraoui et al, 2018;Gupta et al, 2018;Mirman et al, 2018;Noordermeer et al, 2018;Setiaputra & Durocher, 2019). 53BP1 generates sizeable chromatin domains, which scaffold the assembly of downstream effectors and shield DNA lesions against excessive nucleolytic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…53BP1 generates sizeable chromatin domains, which scaffold the assembly of downstream effectors and shield DNA lesions against excessive nucleolytic digestion. Restrained resection is achieved by 53BP1dependent recruitment of RIF1, REV7, and the Shieldin complex (Dev et al, 2018;Findlay et al, 2018;Ghezraoui et al, 2018;Gupta et al, 2018;Mirman et al, 2018;Noordermeer et al, 2018;Setiaputra & Durocher, 2019). Additionally, 53BP1 promotes cell cycle checkpoint signaling in response to DNA damage (DiTullio et al, 2002;Fernandez-Capetillo et al, 2002;Wang et al, 2002;Brummelkamp et al, 2006;Cuella-Martin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA damage response factor 53BP1 is a multi-domain protein comprising of an N-terminal domain with 28SQ/TQ potential phosphorylation sites for phosphatidylinositol 3-related kinases such as ATM/ATR, an oligomerization domain, an H4K20me2-binding Tudor domain, and C-terminal tandem BRCT domains. Recent studies have demonstrated that, in response to AID-instigated lesions, 53BP1 accumulates at Igh DSBs, recruits its phospho-dependent interactor Rif1 (Di Virgilio et al, 2013), and in conjunction with the single-stranded DNA-stabilizing REV7-SHLD1-SHLD2-SHLD3 (shieldin) and CTC1-STN1-TEN1 (CST) complexes, protects S region DSBs from excessive end resection (Setiaputra and Durocher, 2019). However, while 53BP1-Rif1 interaction was thought to play an indispensable role in enforcing NHEJ by limiting resection, there was no direct experimental evidence that the 53BP1-Rif1 interaction is indeed critical for CSR.…”
mentioning
confidence: 99%